2014
DOI: 10.1007/s00253-014-6257-7
|View full text |Cite
|
Sign up to set email alerts
|

Development of Lactobacillus paracasei harboring nucleic acid-hydrolyzing 3D8 scFv as a preventive probiotic against murine norovirus infection

Abstract: The protein 3D8 single-chain variable fragment (3D8 scFv) has potential anti-viral activity due to its ability to penetrate into cells and hydrolyze nucleic acids. Probiotic Lactobacillus paracasei engineered to secrete 3D8 scFv for oral administration was used to test the anti-viral effects of 3D8 scFv against gastrointestinal virus infections. We found that injection of 3D8 scFv into the intestinal lumen resulted in the penetration of 3D8 scFv into the intestinal villi and lamina propria. 3D8 scFv secreted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 40 publications
1
32
0
Order By: Relevance
“…Although we did not intend for the CEFs to express such low levels of 3D8 scFv protein, 3D8 scFv anti-viral activity in transgenic CEFs was detectable. Recently, we have expanded our research towards investigating the role of 3D8 through control of anti-viral effect against H1N1 influenza virus and MNV 22, 23 . Thus, we suppose that low level of 3D8 scFv expression could alleviate initial stage of viral propagation.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not intend for the CEFs to express such low levels of 3D8 scFv protein, 3D8 scFv anti-viral activity in transgenic CEFs was detectable. Recently, we have expanded our research towards investigating the role of 3D8 through control of anti-viral effect against H1N1 influenza virus and MNV 22, 23 . Thus, we suppose that low level of 3D8 scFv expression could alleviate initial stage of viral propagation.…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillus spp. were used to secrete 6 µg L −1 of Guy’s 13 scFv against a streptococcal adhesion molecule [69], 410 µg L −1 of codon-optimized antiviral 3D8 scFv [70] and 1 mg L −1 of an of llama heavy-chain (VHH) antibody fragment against rotavirus [71]. …”
Section: Discussionmentioning
confidence: 99%
“…Category S (function unknown, 6.57%) was also abundant. with an LDH (lactose dehydrogenase) constitutive promoter [9]. Then we used the chloramphenicol resistant gene to measure the survival rate and retention time of the administered Lactobacillus, as shown in Fig.…”
Section: Characterization Of a Novel Strain Using High-throughput Seqmentioning
confidence: 99%
“…In our previous study, we found that, after administration of transgenic Lactobacillus paracasei ATCC 334 expressing the 3D8 scFv (single chain variable fragment) protein to mice, the population of Helicobacter species in the intestine decreased, and the population of Pediococcus acidilactici (a probiotic) increased [8]. In addition, transgenic L. paracasei ATCC 334 showed antiviral efficacy against murine norovirus (MNV) [9]. However, the cheese-derived Lactobacillus is expected to have relatively short persistence and survival in the intestine, which can weaken its probiotic effects.…”
Section: Introductionmentioning
confidence: 99%